Origin of surface motor unit potentials in hypothenar motor unit number estimation. Issue 2 (5th February 2013) - Kawamura, Yasuomi; Sonoo, Masahiro; Higashihara, Mana; Chiba, Takashi; Hatanaka, Yuki
ABSTRACT Introduction: Far‐field potentials (FFPs) from muscles other than the abductor digiti minimi (ADM) may interfere with motor unit number estimation (MUNE) from that muscle. Methods: We identified the origin of each surface motor unit potential (SMUP) during hypothenar MUNE using the multiple point stimulation method in 20 control subjects by recording from individual ulnar‐innervated muscles with a common proximal reference (pref). Results: ADM SMUPs comprised 39.0% of the accepted SMUPs, followed by those from the fourth dorsal interosseous muscle (14.0%), the fourth lumbrical muscle (9.2%), and the second and third palmar interosseous muscles (8.8% each). The percentage of ADM SMUPs varied from 18% to 73% of accepted SMUPs among individual subjects. Accepted non‐ADM SMUPs were usually much smaller than ADM SMUPs, and many more non‐ADM SMUPs were excluded due to their small size. Conclusions: A large contribution from non‐ADM or non‐hypothenar SMUPs obscures the meaning of the MUNE value. Muscle Nerve, 48: 185–190, 2013